Health literacy, preventive COVID 19 behaviour and adherence to chronic disease treatment during lockdown among patients registered at primary health facility in urban Jodhpur, Rajasthan. Issue 1 (January 2021) - Gautam, Vaishali; S, Dileepan; Rustagi, Neeti; Mittal, Ankit; Patel, Mehul; Shafi, Shazia; Thirunavukkarasu, Prasanna; Raghav, Pankaja
Abstract: Background and aims: Potential role of health literacy in determining adherence to COVID-19 preventive behavior, pharmacological, and lifestyle management among diagnosed patients of chronic diseases during nationwide lockdown is inadequately investigated. Methods: A cross-sectional study was conducted from May–August 2020 among diagnosed patients of chronic diseases residing in a COVID-19 hotspot of urban Jodhpur, Rajasthan, and availing health services from primary care facility. Telephonic interviews of participants were conducted to determine their health literacy using HLS-EU-Q47 questionnaire, adherence to COVID-19 preventive behaviour as per World Health Organization recommendations, and compliance to prescribed pharmacological and physical activity recommendations for chronic disease. Results: All the 605 diagnosed patients of chronic diseases availing services from primary care facility were contacted for the study, yielding response rate of 68% with 412 agreeing to participate. Insufficient health literacy was observed for 65.8% participants. Only about half of participants had scored above median for COVID-19 awareness (55.1%) and preventive behavior (45.1%). Health literacy was observed to be significant predictor of COVID-19 awareness [aOR: 3.53 (95% CI: 1.81–6.88)]; COVID-19 preventive behavior [aOR: 2.06, 95%CI; 1.14–3.69] and compliance to pharmacological management [aOR: 3.05; 95% CI: 1.47–6.35] but not for physical activity. Conclusion: COVID-19 awareness, preventive behavior, and compliance to pharmacological management is associated with health literacy among patients of chronic disease availing services from primary health facility. Focusing on health literacy could thus be an essential strategic intervention yielding long term benefits. Highlights: Majority (65.8%) of chronic disease patients availing care from the primary level possess insufficient Health literacy. Health literacy is an important predictor of COVID-19 preventive behaviour and adherence to pharmacological management. Enhancing health literacy of chronic disease patients availing care from the primary level require attention in India.